Konsep Wisata Halal dan Hak-hak Wisatawan dalam Perspektif Fikih: The Concept of Halal Tourism and The Tourist Rights in an Islamic Jurisprudence Perspective - Bakhrul Huda (El-Qist: Journal of Islamic Economics and Business (JIEB), 2022)
Abstract: This study aims to answer what are the provisions of Halal Tourism from the perspective of Fiqh? How can a tourist area be said to be halal (permitted in Islam)?, and what are the rights of tourists to Halal Tourism destinations?. By using non-interactive qualitative research, data in this study were collected from the verses of the Qur'ān, Matan Hadīth, Maqālah (statement and opinion) of the Moslem scholars regarding the explanations of these verses and Hadīth, also articles and proceedings relevant to the theme. The result of the study is that tourism can be categorized in the halal category as long as it does not leave one of the following destinations; going to Ḥaram (The Sacred Mosque), connecting kinship, visiting Ulamā’ or pious people, recreation for body and soul refreshment, fulfilling invitations or shar'ī events, service or work and da'wah. A tourist area can be categorized as a halal by fulfilling the following conditions; facilities of worship are available, there are no haram or munkar facilities, there is no haram food and drink, giving a tourists rights, there is no injustice, environmentally friendly, preserves local norms and values ​​as long as it does not conflict with sharia values. Meanwhile, the rights of tourists visiting the Halal Tourism area are; getting life protection, getting access to worship, guaranteed luggage safety, getting the facilities offered, and being protected from injustice. Keywords: Halal Tourism Concept; Halal Tourism Area; Tourist Rights; Fiqh   Abstrak: Penelitian dalam artikel ini ingin menjawab bagaimana ketentuan Wisata Halal dalam perspektif Fikih? Bagaimana area wisata dapat dikatakan halal?, dan apa hak-hak wisatawan destinasi Wisata Halal?. Dengan menggunakan penelitian kualitatif non-interaktif, data dikumpulkan dari Ayat al-Qur’an, Matan Hadis, maqālah para ulama tentang penjelasan Ayat dan Hadis tersebut, artikel dan prosiding yang relevan dengan tema. Hasilnya, bahwa Wisata dapat masuk kategori Halal selama tidak keluar dari salah satu tujuan berikut; pergi ke Tanah Haram, silaturrahim, menziarahi Ulama atau orang saleh, rekreasi penyegaran jiwa dan raga, memenuhi undangan atau acara yang shar‘ī, dinas atau kerja dan dakwah. Sebuah area wisata dapat dikatakan Halal jika memenuhi semua ketentuan sebagai berikut, yaitu; tersedia sarana ibadah, tidak ada fasilitas haram atau munkar, tidak ada makanan-minuman haram, memberikan hak-hak wisatawan, tidak ada kezaliman, ramah lingkungan, melestarikan norma dan nilai setempat selama tidak bertentangan dengan syariah. Sedangkan hak-hak wisatawan yang berkunjung di area Wisata Halal adalah; mendapat perlindungan jiwa, mendapatkan akses ibadah, terjamin keamanan barang bawaan, mendapatkan fasilitas yang ditawarkan, dan terjaga dari kezaliman. Kata Kunci: Konsep Wisata Halal; Area Wisata Halal; Hak Wisatawan; Fikih